Inhibition of Metastatic Potential in Breast Carcinoma In Vivo and In Vitro through Targeting VEGFRs and FGFRs. (3rd June 2013) - Chien, Ming-Hsien; Lee, Liang-Ming; Hsiao, Michael; Wei, Lin-Hung; Chen, Chih-Hau; Lai, Tsung-Ching; Hua, Kuo-Tai; Chen, Min-Wei; Sun, Chung-Ming; Kuo, Min-Liang
Abstract : Angiogenesis and lymphangiogenesis are considered to play key roles in tumor metastasis. Targeting receptor tyrosine kinases essentially involved in the angiogenesis and lymphangiogenesis would theoretically prevent cancer metastasis. However, the optimal multikinase inhibitor for metastasis suppression has yet to be developed. In this study, we evaluated the effect of NSTPBP 0100194-A (194-A), a multikinase inhibitor of vascular endothelial growth factor receptors (VEGFRs)/fibroblast growth factor receptors (FGFRs), on lymphangiogenesis and angiogenesis in a mammary fat pad xenograft model of the highly invasive breast cancer cell line 4T1-Luc + . We investigated the biologic effect of 194-A on various invasive breast cancer cell lines as well as endothelial and lymphatic endothelial cells. Intriguingly, we found that 194-A drastically reduced the formation of lung, liver, and lymph node metastasis of 4T1-Luc + and decreased primary tumor growth. This was associated with significant reductions in intratumoral lymphatic vessel length (LVL) and microvessel density (MVD). 194-A blocked VEGFRs mediated signaling on both endothelial and lymphatic endothelial cells. Moreover, 194-A significantly inhibited the invasive capacity induced by VEGF-C or FGF-2 in vitro in both 4T1 and MDA-MB231 cells. In conclusion, these experimental results demonstrate that simultaneous inhibition of VEGFRs/FGFRs kinases may be a promising strategy to prevent breast cancer metastasis.